Optimization of Technology in the Development of Citengah Village - Ahmad Geohansa; Eeng Sumarna; Mulyaningsih (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Citengah Village in Sumedang Selatan District has great potential in sustainable development, especially through the use of digital technology. This study aims to analyze the readiness of Citengah Village in implementing technology, identify the main obstacles, and formulate appropriate technology optimization strategies. Using the Smart Village approach, which emphasizes the integration of technology to improve the efficiency of village governance, this study also utilizes the theory of development administration as an analytical framework to measure transparency, participation, and accountability in village development. The results of the study indicate that Citengah Village has a strategic vision for digitalization through the RPJMDes, but limited digital infrastructure, low technological literacy of village officials, and limited budget are the main obstacles. The proposed strategies include strengthening internet infrastructure, intensive training for village human resources, and collaboration with external parties to support funding and technology. This study emphasizes the importance of the relationship between the Smart Village approach and development administration. Technology not only improves the efficiency of public services but also supports more inclusive and accountable village governance. By implementing this optimization strategy, Citengah Village has the potential to become a model of a technology-based village that is able to answer community needs in a sustainable manner.